E-115 Treatment strategies for acute thrombus in cervical carotid and vertebral arteries without intracranial occlusion at presentation with stroke symptoms. (22nd July 2018) - Donegan, B; Akhtar, I; Halpin, J; Martin, C; Holloway, W; Akhtar, N
Abstract : Introduction and purpose: Time and again we come across cases of acute intraluminal thrombus in the proximal carotid and vertebral arteries without intracranial involvement. They are particularly challenging as the risk of dislodging the thrombus with intervention is high and can result in a potentially worse stroke. We present our experience of seven patients with an acute thrombus in their cervical arteries. The aim of this presentation is to demonstrate the diversity of managements in these patients. Materials and methods: We retrospectively reviewed cerebral angiography reports spanning 8 years at our institution retaining cases showing thrombus in carotid or vertebral arteries. With identified cases, medical records were reviewed for stroke presentation, severity, and management. A total of 7 cases were identified. There were four patients with a thrombus in the proximal internal carotid artery and three patients with a thrombus in the proximal vertebral arteries. In all of these cases, the thrombus was due to underlying severe stenosis of the ICA/vertebral origins and was seen on catheter angiogram and CT angiogram as filling defects within the lumen of these vessels. Results: 3 patients (2 carotid, 1 vertebral) were treated medically–2 with anticoagulant therapy (heparin/coumadin) in 1 with Aspirin/Clopidogrel. All 3 were admitted to the Intensive Care Unit and closely monitored until there was complete resolution of the acute clot on follow up imaging. Of these 3 patients, 2 patients underwent angioplasty/stenting and 1 patient underwent endarterectomy electively for underlying critical stenoses. 2 patients with an ICA thrombus showed changes of acute/subacute strokes on presenting CT and were considered to be unsuitable for anticoagulation. They were treated with angioplasty and stenting with distal embolic protection. In one patient, the thrombus was successfully trapped within the stent while in the other patient, part of the thrombus embolized to the middle cerebral artery and was subsequently retrieved with a stent retriever. In one patient with a vertebral thrombus, anticoagulation was started but the patient showed evidence of intracranial embolization with new strokes on MRI within the first 24 hours and angioplasty and stenting was performed acutely with no complications. In one patient with vertebral thrombus, anticoagulant therapy was started but the clot embolized into the basilar artery within 1 hour of the start of treatment with significant neurological worsening. No further treatment was performed per family request and the patient died in 48 hours. Conclusion: The treatment for acute intraluminal thrombus in the major vessels is very challenging, as the situation is very fluid and can change for worse if the clot embolizes. These patients should be closely observed and the treatment should be customized according to the clinical situation. Disclosures: B. Donegan: None. I. Akhtar: None. J. Halpin: None. C. Martin: None. W. Holloway: None. N. Akhtar: None.